2015
DOI: 10.3390/coatings5030557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Cure on the Thermo-Mechanical Properties of Tung Oil-Based/Carbon Nanotube Composites

Abstract: Tung oil is uniquely reactive among plant-based natural oils due to the series of conjugated carbon-carbon double bonds in its fatty acid chains. These conjugated carbon-carbon double bonds impart a high reactivity towards cationic polymerization in the presence of other reactive co-monomers, such as divinylbenzene and styrene. An impressive decrease in the cure time of tung oil-based thermosets has been achieved when the resins investigated were microwaved in the presence of carbon nanotubes (CNTs). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…F50-T50-F showed a higher storage modulus (540 MPa) than F40-T60-F (340 MPa) and F30-T70-F (60MPa) at room temperature (Table 2). These values are comparable to the reported storage modulus values of other tung oil polymers [2,9,25]. It was difficult to run F30-T70-F samples, as these samples were too brittle to continue in tension mode, and broke above 45 °C.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…F50-T50-F showed a higher storage modulus (540 MPa) than F40-T60-F (340 MPa) and F30-T70-F (60MPa) at room temperature (Table 2). These values are comparable to the reported storage modulus values of other tung oil polymers [2,9,25]. It was difficult to run F30-T70-F samples, as these samples were too brittle to continue in tension mode, and broke above 45 °C.…”
Section: Resultssupporting
confidence: 83%
“…The broad range of peaks in the 5.5-6.5 ppm (highlighted with green square shape in Figure 10a) region suggested a conjugated triene structure for TO, which was absent in soluble portions of FMA-TO polymers [32]. The absence of any characteristic peaks of FMA in the 5-6 ppm region confirmed that the predominant TO-related compounds in the soluble portions of FMA-TO polymers might be TO oligomers [2]. A similar conclusion was reached from 13 C spectra of FMA-TO polymers, as the TO-related carbon predominated in the 120-150 ppm and 10-40 ppm regions (highlighted with a green square shape in Figure 10b).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations